1979
DOI: 10.1002/pen.760190710
|View full text |Cite
|
Sign up to set email alerts
|

Compatible glassy polyblends based upon poly(2,6‐dimethyl‐1,4‐phenylene oxide): Tensile modulus studies

Abstract: The mechanical behavior of compatible glassy polyblends based upon poly(2.6‐dimethyl‐ 1,4‐phe nylene oxide) (PPO) was investigated. In particular, the influence of composition, molecular weight, and molecular weight distribution upon the tensile modulus of the blend was assessed. Various possible correlations between the experimentally determined moduli and theory are considered. Included are correlations with density, packing density, composite theory, and lattice fluid theory. The modeling of the properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 18 publications
5
38
0
Order By: Relevance
“…Previous work by Ishiaku et al 5 on PVC/ENR blends also showed that the relationship between low temperature storage modulus and composition of the blend positively deviated from the rule of mixture, but corresponded well to the Kleiner equation. 30 Similar results were also observed in polystyrene (PS)/poly(2,6-dimethyl 1,4-phenylene oxide) (PPO) blend 31 and PVC/NBR blend.…”
Section: Extrudate Characteristicssupporting
confidence: 79%
“…Previous work by Ishiaku et al 5 on PVC/ENR blends also showed that the relationship between low temperature storage modulus and composition of the blend positively deviated from the rule of mixture, but corresponded well to the Kleiner equation. 30 Similar results were also observed in polystyrene (PS)/poly(2,6-dimethyl 1,4-phenylene oxide) (PPO) blend 31 and PVC/NBR blend.…”
Section: Extrudate Characteristicssupporting
confidence: 79%
“…A review of these studies, including possible causes for the synergistic effects, is available [5]. Examples of miscible polymer blends showing synergistic effects are blends of poly(phenylene oxide)(PPO) and polystyrene (PS) [6]. Modulus values of these blends are higher than those anticipated according to the rule of mixtures at all compositions, and the maximum value of the modulus appears to occur at a PPO content of 20 -25 wt% [6].…”
Section: Introductionmentioning
confidence: 96%
“…The parameter ␤ 12 (200 MPa in this blend) quantifies the deviation and has been tentatively related to the compatibility of the blend. 36 Although a possible suppression of a low temperature secondary transition should also be taken into account, 44 the ␤ 12 values range between 200 and 2000 MPa in thermoplastic/thermoplastic blends both when the modulus synergism is attributed to volume contractions 17,36,44 and when it is attributed to higher orientation of any of the components in the blends. 45 However, values of roughly 2500 MPa or higher are obtained in thermoplastic/liquid crystalline polymer (LCP) 46 and LCP/LCP blends, 47 due to the large orientation of the LCPs.…”
Section: As-molded Blendsmentioning
confidence: 99%
“…As in a previous work, 32 a small synergism was observed at all blend compositions. Synergisms in the modulus are usual in miscible blends, [35][36][37] in partially miscible blends, 32,38,39 and also in reacted blends. 24,40 However, some immiscible blends 41,42 also showed synergisms in the modulus.…”
Section: As-molded Blendsmentioning
confidence: 99%